A Qualitative Study on Improving Test Outcomes Through Reading Strategy Instruction in the Educational Context - Zhang, Miao (Pacific International Journal, 2025)
This qualitative study explores the impact of reading strategy instruction on improving test outcomes among middle school students at Harbin Qunli Jingwei Middle School, China. The study investigates how structured reading strategies, such as predicting, summarizing, questioning, and visualizing, influence students' reading comprehension and academic performance. Data were collected through semi-structured interviews with teachers and students, along with classroom observations. The findings indicate that students who received explicit instruction in reading strategies demonstrated increased confidence, higher test scores, and better engagement with complex texts. Teachers who frequently implemented reading strategies observed greater student participation and improved test performance. However, challenges such as time constraints and limited teacher training in strategy-based instruction were also noted. The study suggests that integrating reading strategies into the curriculum, providing ongoing professional development for teachers, and fostering student autonomy in strategy use can significantly enhance test outcomes. The findings highlight the importance of reading strategy instruction in both academic achievement and overall literacy development.